PERANCANGAN PROTOTYPE PENDAFTARAN SERVICE HANDPHONE BERBASIS WEBSITE MENGGUNAKAN MEDIA FIGMA - Wijaya, Ricky Junianto; Nugroho, Isaac Yeremia; Alexander, Edwin (Jurnal Informatika UPGRIS, 2024)
Abstract— The rapid evolution of information technology has revolutionized various aspects of daily life, particularly in the business domain. Ms. Joulla Mellani's mobile phone service business, situated in East Surabaya, strives to adapt to these changes. This project focuses on developing a Figma-based website prototype for efficient and accessible mobile phone service registration. Traditionally, promotional efforts were reliant on flyers, leading to inefficiencies. Customers faced challenges contacting the service, resulting in uncertainty about their queue status. The limited availability of the owner on WhatsApp further impeded service processes. The research, employing literature review, observation, and interviews, utilized the Waterfall method for website development. The outcome is a user-friendly website streamlining service registration, enhancing data management, and broadening promotional outreach. Both the business owner and customers will benefit from this platform. In conclusion, the Figma-based website design effectively addresses the business challenges faced by Ms. Joulla Mellani, optimizing the mobile phone service process.